Parties at war : political organization in Second World War Britain - Thorpe, Andrew 1962- (Oxford Univ. Press, 2009)
The Second World War represented the most sustained challenge to the British party system during the 20th century. This text explores how the main political parties responded to this challenge, showing that struggles over organisation had significance for the long-term development of 'party' in modern British politics.